Penerapan Balanced Scorecard Dalam Penyusunan Rencana Strategi Bisnis (RSB) Tahun 2020-2024 Di Rumah Sakit Jiwa X Magelang - Supramono Supramono (Program Studi Magister Manajemen Rumah Sakit, Jenjang Pasca Sarjana (S2), Pasca Sarjana Universitas Muhammadiyah Yogyakarta, 2020)
This research uses a qualitative approach through descriptive analysis of the application of the balanced scorecard in the preparation of a business strategy plan for the mental hospital X Magelang 2020-2024. The results showed that based on the SWOT analysis conducted by active observation methods, group discussion forums (FGD) and documentation studies produced vision, mission and organizational values which were then translated into strategic targets, key performance indicators and targets all based on a balanced scorecard that is divided into four learning and growth perspectives, internal business processes, customers, and finance as well as with key performance indicators / Key Performance Indicators (KPI) on each strategic goal. The competitive position of the hospital is in quadrant II so that the strategic steps taken are maintaining organizational stability or strengthening organizational quality by improving organizational governance, management system capabilities, hospital management information systems, business processes and building organizational culture. Required joint commitment from all levels in the mental hospital. X Magelang to implement the Business Strategy Plan (RSB) based on the balanced scorecard period 2020-2024 and periodically evaluate the performance of each perspective.